Experimental and theoretical aspects of the stabilization of zirconia. - Bechepeche, A. P.; Treu, O.; Longo, Elson [UNESP]; Paiva-Santos, C. O.; Varela, José Arana [UNESP] (Kluwer Academic Publ, 1999)
Using the Rietveld method, phases of ceria-doped zirconia, calcined at temperatures of 600 and 900 degrees C, were quantitatively analysed for different concentrations of ceria. The results show that the stabilization of zirconia depends on the dopant concentration and calcination temperature. Moreover, the theoretical calculation using the ab initio Hartree-Fock-Roothaan method indicates that the most stable phases for ceria-stabilized zirconia are cubic or tetragonal, in accordance with experimental results. (C) 1999 Kluwer Academic Publishers.